Cognitive deficits in individuals with methamphetamine use disorder: A meta-analysis. (May 2018) - Potvin, Stéphane; Pelletier, Julie; Grot, Stéphanie; Hébert, Catherine; Barr, Alasdair M.; Lecomte, Tania
Abstract: Background: Methamphetamine has long been considered as a neurotoxic substance causing cognitive deficits. Recently, however, the magnitude and the clinical significance of the cognitive effects associated with methamphetamine use disorder (MUD) have been debated. To help clarify this controversy, we performed a meta-analysis of the cognitive deficits associated with MUD. Methods: A literature search yielded 44 studies that assessed cognitive dysfunction in 1592 subjects with MUD and 1820 healthy controls. Effect size estimates were calculated using the Comprehensive Meta-Analysis, for the following 12 cognitive domains: attention, executive functions, impulsivity/reward processing, social cognition, speed of processing, verbal fluency/language, verbal learning and memory, visual learning and memory, visuo-spatial abilities and working memory. Results: Findings revealed moderate impairment across most cognitive domains, including attention, executive functions, language/verbal fluency, verbal learning and memory, visual memory and working memory. Deficits in impulsivity/reward processing and social cognition were more prominent, whereas visual learning and visuo-spatial abilities were relatively spared cognitive domains. A publication bias was observed. Discussion: These results show that MUD is associated with broad cognitive deficits that are in the same range as those associated with alcohol and cocaine use disorder, as recently shown by way of meta-analysis. The prominent effects of MUD on social cognition and impulsivity/reward processing are based on a small number of studies, and as such, these results will need to be replicated. The functional consequences (social and occupational) of the cognitive deficits of methamphetamine will also need to be determined. Highlights: Our meta-analysis reveals that methamphetamine use disorder is associated with moderate impairment in 7 cognitive domains. Deficits in impulsivity/reward processing and social cognition were more prominent. By comparison, visuo-spatial abilities were relatively spared.